(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article presents the results of studies on the use of phosphorus-containing fertilizers from Kyzylkum phosphorites on typical old-irrigated serozem soils of the Zerafshan oasis of the Republic of Uzbekistan. The optimal rates of application of Rncfu at the rate of 100-140 kg / ha P2O5, contributing to obtaining a stable yield of onion of good quality, have been determined. Equivalent value of new forms of phosphorus-containing fertilizers has been established.